Issues and Challenges on Khairat Death Fund Management:Case Study of Khairat Death Fund Organizations in Malaysia - Nuur Halimatus Saadiah Masrukhin; Azrul Azlan Iskandar Mirza; Khairil Faizal Khairi; Syadiyah Abdul Shukor (UNIVERSITAS ISLAM BANDUNG & RESEARCH SYNERGY FOUND, 2024)
International Journal of Emerging Issues in Islamic Studies (IJEIIS) ISSN 2807-2049(Online)| 2807-2057 (Print) Volume 2Number 1(Year): 91-97